(3GdeQCI GdeUQjI GdeYGUQI aj GdHQdeGfs (3fGFHI JaNQ HgG eUQs - (3eUQ, GdeLdS GdCYdi ddKbGaIs; (3YUahQ, LGHQs ((3GdbGgQIs (3GdeLdS GdCYdi ddKbGaIs, 2009)
(3GdcJGH jJcde Yf eKd eTQa ddeQCI GdeUQjI ai GdSdWI GdJTQjYjI hgi fGFHI ai GdHQdeGf GdeUQi hJbdOJ efGUH YGdejI CNQi MjK jHQR GdcJGH OhQgG GdaYGd ai gPg GdefGUH eOYeG HGdUhQ GdTNUjI ai cd aUds
(3GdeMJhjGJ (B: (3ai eLdS GdTYH (B-- (3efGUH HQdeGfjI OhdjI (B-- (3eY GdbjGOGJ GdOhdjI (B-- (3ehGba hCbhGd eSLdIs
1 2 13 14 18
Keywords: (3GdSjGSjhf GdeUQjhfs -- (3JQGLes; (3GdeQCI aj GdSjGSIs